Cross-resistance pattern to four AHAS-inhibiting herbicides of tribenuron-methyl-resistant flixweed (Descurainia sophia) conferred by Asp-376-Glu mutation in AHAS - Wei DENG; Qian YANG; Hong-tao JIAO; Yong-zhi ZHANG; Xue-feng LI; Ming-qi ZHENG (Journal of Integrative Agriculture, 2016)
Flixweed (Descurainia sophia L.) is a problematic and widespread weed in winter wheat fields and has been controlled by tribenuron-methyl for more than twenty years in China. In this study, a flixweed accession (Hebei 25, HB25) with an Asp-376-Glu mutation in acetohydroxy acid synthase (AHAS) was identified and purified. The purified HB25 accession (pHB25) developed 758.1-fold resistance to tribenuron-methyl and exhibited obvious cross-resistance to four AHAS-inhibiting herbicides. The resistant/susceptible (R/S) ratios of 50% plant growth reduction (GR50) to herbicides of halosulfuron-methyl, flumetsulam, imazethapyr and pyribenzoxim were 346.1, 15.7, 8.1 and 7.1, respectively. The reduced AHAS sensitivities to four different AHAS-inhibiting herbicides, which were caused by the Asp-376-Glu mutation, were responsible for the resistance and cross-resistance to AHAS-inhibiting herbicides. The R/S ratios of 50% inhibition of AHAS activity (I50) to tribenuron-methyl, halosulfuron-methyl, flumetsulam, imazethapyr and pyribenzoxim were 844.5, 532.9, 74.5, 13.3 and 5.5, respectively. The results of AHAS activity in vitro were highly correlated with that of whole-plant response experiments.